Analysis Of Bench Crest Performance At The Yellowstone Mine: A Case Study - J. Whyatt; M. MacLaughlin (The National Institute for Occupational Safety and Health (NIOSH))
A case study is presented that relates statistical descriptions of joint sets to the distribution of local wedge failures along the crest of a catch bench at the Yellowstone Talc Mine. The fracture sets and bench width were mapped by teams of geological engineering students from Montana Tech under the direction of Dr. Mary MacLaughlin. The students analyzed the fracture data, conducted physical property tests, and used a beta version of a NIOSH program “Bwedge” to predict the distribution of surviving bench widths. In the course of this analysis the students developed evidence of software performance issues that, unfortunately, frustrated their analysis. These have now been addressed and a full analysis completed. The analysis confirms the validity of the student mapping program and provides insight into the effects of blasting and excavation practices on the bench. It also provides a tool for exploring the pattern of bench crest failure that would result from variations in both bench geometry and blasting practices.